Conceptualising the inspirational effect of elite sport: a case study of field hockey in Belgium - de Cocq, S.; Derom, I.; De Bosscher, V. (European Sport Management Quarterly, 2021)
This study aims to better understand and conceptualise the dynamics of inspirational elite sport. Specifically, taking Belgian hockey as a case study, this article is concerned with understanding how, why, and under what circumstances elite sport influences grassroots sport participation in voluntary sports clubs (i.e. trickle-down effect). Research methods